1993
DOI: 10.1007/bf00178260
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific 1H and 15N resonance assignments and secondary structure of GDP-bound human c-Ha-Ras protein in solution

Abstract: All the backbone 1H and 15N magnetic resonances (except for Pro residues) of the GDP-bound form of a truncated human c-Ha-ras proto-oncogene product (171 amino acid residues, the Ras protein) were assigned by 15N-edited two-dimensional NMR experiments on selectively 15N-labeled Ras proteins in combination with three-dimensional NMR experiments on the uniformly 15N-labeled protein. The sequence-specific assignments were made on the basis of the nuclear Overhauser effect (NOE) connectivities of amide protons wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 83 publications
2
22
0
Order By: Relevance
“…13,[22][23][24][25][26] The binding of GTP to Ras causes a conformational change in two regions, commonly referred to as switch I (residues [32][33][34][35][36][37][38][39][40] and switch II (residues 58-75). [27][28][29] The GTP-dependent conformation of switch I is critical for high affinity interaction between Ras and the Raf-RBD.…”
Section: Introductionmentioning
confidence: 99%
“…13,[22][23][24][25][26] The binding of GTP to Ras causes a conformational change in two regions, commonly referred to as switch I (residues [32][33][34][35][36][37][38][39][40] and switch II (residues 58-75). [27][28][29] The GTP-dependent conformation of switch I is critical for high affinity interaction between Ras and the Raf-RBD.…”
Section: Introductionmentioning
confidence: 99%
“…This was justifying the applicability of the parameters for the forthcoming measurements. Commonly, the NMR studies on the Ras protein revealed higher unstructured contents which were counterbalanced by roughly equal amounts of diminishes in other structural elements, while the overall structures were mainly consistent with the crystal structures [123,124]. This information was pointing at the contribution of the protein dynamics enhancement in solution.…”
Section: Curve-fit Resultsmentioning
confidence: 77%
“…This was making part of the β-sheet structure flexible and the information was contrasting to the rigidity in crystalline states [126]. In relation, it was suggested [123] that the salt bridge between D33 of one Ras protein molecule and R135 of another symmetryrelated molecule in the crystalline state [126] was stabilizing the loop L2 conformation and the end of antiparallel β-strand β2. Besides, the residue N26 which was found to be essential for the signal transducing activity of Ras [136], was exhibiting a flexible nature in solution [123].…”
Section: Oligomerization;mentioning
confidence: 99%
See 2 more Smart Citations